2018
DOI: 10.2147/ijn.s164866
|View full text |Cite
|
Sign up to set email alerts
|

Rho GTPases in A549 and Caco-2 cells dominating the endocytic pathways of nanocarbons with different morphologies

Abstract: IntroductionEndocytosis of nanomaterials is the first step of nano-bio interaction and current regulation is mostly by nanomaterials but seldom by intracellular signaling proteins.Materials and methodsHerein, we synthesized tubular nanocarbon (oxMWCNT) and lamellar-like nanocarbon (oxGRAPHENE) and formulated their aqueous dispersion. A549 and Caco-2 cells were selected as the models of tumor and intestinal epithelial cells, respectively. After knocking down three members of Rho GTPases (Cdc42, Rac1, RhoA) in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…At the same time, these hybrids increase the mitochondrial metabolism of normal colon cells, improving the cell viability between 200% and 400% in the studied concentration range. We postulate that this unprecedented differential effect of the SWCNT-NCC(II) hybrid on normal and cancer Caco-2 cells, respectively, could be related to its unique morphology, that might trigger different uptake pathways, 51 have been studied in detail in order to tailor the nanocellulose type (from nearly pure type-I to nearly pure type-II, including their mixtures) without the need for mercerization or re-crystallization. Their characterization revealed that such type-II NCC (exclusively coming from acid hydrolysis) presents larger hydrodynamic sizes and sulfate content, leading to unique properties comparted to their mercerized analogues.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, these hybrids increase the mitochondrial metabolism of normal colon cells, improving the cell viability between 200% and 400% in the studied concentration range. We postulate that this unprecedented differential effect of the SWCNT-NCC(II) hybrid on normal and cancer Caco-2 cells, respectively, could be related to its unique morphology, that might trigger different uptake pathways, 51 have been studied in detail in order to tailor the nanocellulose type (from nearly pure type-I to nearly pure type-II, including their mixtures) without the need for mercerization or re-crystallization. Their characterization revealed that such type-II NCC (exclusively coming from acid hydrolysis) presents larger hydrodynamic sizes and sulfate content, leading to unique properties comparted to their mercerized analogues.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, these hybrids increase the mitochondrial metabolism of normal colon cells, improving the cell viability between 200 and 400% in the studied concentration range. We postulate that this unprecedented differential effect of the SWCNT−NCC(II) hybrid on normal and cancer Caco-2 cells could be related to its unique morphology, which might trigger different uptake pathways, 51 with a different response depending on the cell metabolism. The unexpected activation of normal cell metabolism could be related to this fact, as it might have promoted an enhancement of mitochondrial activity through its own uptake pathway.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Data of liquid chromatography-tandem mass spectrometry (LC-MS/MS) with normalization to protein content revealed that, compared with the deciliated MEFs, the ciliated MEFs are enriched in acetylated tubulin (Ac-Tub) and Arl13b, two markers for primary cilia 23 , 24 , and IFT88 and KIF3A as well, two molecules pivotal to the maintenance and function of primary cilia 25 , 26 (Figure 1 C). Intriguingly, among the three members in Rho family of small GTPases 27 , only enrichment of Rac1 but not Cdc42 or RhoA was observed in the ciliated MEFs, compared with that in deciliated MEFs (Figure 1 C), and the enrichment of Rac1 in MEF primary cilia was additionally verified by immunnofluorescent staining (Figure 1 D), indicating that Rac1 may affect Hh signaling.…”
Section: Resultsmentioning
confidence: 87%
“…Moreover, uptake of graphene materials by cells have been previously reported [28] , [50] , [51] . Endocytosis is the mechanism suggested by the scientific literature for graphene related materials [15] , [51] , [52] and it is influenced by particle size and surface chemistry [51] . Our results have shown that both, rGO and GO are internalized by Caco-2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…According to this guidance, the first step should be a physico-chemical characterization, and among the toxicity testing required, in vitro studies remain at the basal level, as they can provide insights into a nanomaterial’s hazard and its mode of action. Physico-chemical properties, such as surface charge, size, composition or structure have been demonstrated to have effects on the uptake of graphene materials by cells [15] . Moreover, they can affect the outcome of the risk assessment, as toxicity may change.…”
Section: Introductionmentioning
confidence: 99%